PENGARUH MEDIA PEMBELAJARAN DIGITAL DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X MATA PELAJARAN EKONOMI DI SMAN 1 BARRU - Sri Wahyuni Juika; Mustafa; Syamsu A Kamaruddin (STKIP Subang, 2025)
The rapid development of digital technology has reshaped educational practices, offering various opportunities for students to access learning resources more flexibly and interactively. In Economics learning, which often presents abstract concepts, digital learning media play a central role in helping students visualize economic systems, analyze data, and understand real-world economic phenomena through simulations and multimedia content. This study aims to analyze the influence of digital learning media and learning interest on the learning outcomes of tenth-grade students at SMAN 1 Barru. This quantitative associative research involved 60 students selected through purposive sampling based on their exposure to digital learning media for at least one semester. Data were collected using standardized questionnaires and analyzed through validity tests, reliability tests, linearity tests, simple regression, and multiple regression using SPSS. The results reveal that digital learning media significantly and positively influence students’ learning outcomes, indicating that interactive and multimedia-based learning tools enhance students’ understanding and achievement. Additionally, students’ learning interest demonstrates a strong positive effect on learning outcomes, showing that motivation and engagement are essential determinants of academic success. The simultaneous influence of digital learning media and learning interest was also proven significant. These findings highlight the importance of integrating pedagogically sound digital media with strategies that nurture students’ learning interest to optimize educational outcomes in Economics learning. Keywords: digital learning media, learning interest, learning outcomes